Partisipasi Masyarakat dalam Pengelolaan Sampah Rumah Tangga Berbasis 3R di TPST Desa Ngijo, Malang. - Fahreza Aditia Putra; Sulismadi Sulismadi (Sosietas: Jurnal Pendidikan Sosiologi, 2024)
This research focuses on community participation in 3R-based household waste management (Reduce, Reuse and Recycle) at the Integrated Waste Management Site (TPST) in Ngijo Village, Karangploso District, Malang Regency. The aim is to describe and analyze forms of community participation in waste sorting and recycling, identify factors that influence low participation, and analyze the extent to which TPST is able to build community participation.A qualitative approach was used with observation, in-depth interviews and documentation methods. The research results show that community participation in the construction of the TPST was very large, both in planning, implementation and maintenance. However, in 3R-based waste management, individual participation is still lacking, while group participation through Community Self-Help Groups is very good. This research provides recommendations for increasing individual and group participation in 3R waste management in Ngijo Village.Keywords: Community participation, 3R waste management